3D printed meta-sandwich structures: Failure mechanism, energy absorption and multi-hit capability. (15th December 2018) - Yazdani Sarvestani, H.; Akbarzadeh, A.H.; Mirbolghasemi, A.; Hermenean, K.
Abstract: A new class of lightweight and 3D printable architected sandwich structures, named as meta-sandwich structures, has been introduced. These lightweight sandwich structures, which have been made of mechanical metamaterials as the core, show many advantages such as high stiffness-to-weight ratio and high energy absorption capability. In this paper, finite element simulation and experimental testing were implemented to evaluate the structural durability of 3D printed meta-sandwiches under quasi-static flexure and low-velocity impact tests. We specifically investigated the failure mechanism, energy absorption and multi-hit capability of 3D printed polymeric meta-sandwich structures made of cubic, octet and Isomax cellular cores. Three-point bending experiments on 3D printed meta-sandwich beams were conducted to evaluate their flexural stiffness and quasi-static energy absorption, followed by low-velocity impact tests to determine their dynamic energy absorption and multi-hit capabilities. Analytical formulations were also developed to capture the failure mechanism in the architected sandwich structures. It is found that the core topology and geometrical parameters have significant effects on failure mechanism and energy absorption of meta-sandwich structures. For example, Isomax meta-sandwich structures show high quasi-static and dynamic impact energy absorption capabilities. Graphical abstract: Highlights: A comprehensive study was developed to determine the preferred geometry of architected 3D-printed meta-sandwich structures. We 3D printed architected sandwich beams and plates of different metamaterial cellular cores and conducted quasi-static and low-velocity impact tests. The structures with Isomax metamaterial cellular cores had a higher level of energy absorption capability. A numerical methodology, analytical formulation and experimental testing were developed for a new generation of architected sandwich structures.